Investigating how the sources of online audio Qur’an empower listeners - Zeki, Akram M.; Oyefolahan, Ishaq Oyebisi; Abd Malek,, Nur Azrin; Mahmud, Murni; Mahmood , Nadeem; Shah, Asadullah; Abubakar, Adamu (2014)
Fundamental Islamic principles require that the Qur’an, in whatever format, should remain intact. The Internet is a huge source of different formats of the Qur’an. Unfortunately some people are skeptical about the content of any Islamic resource on the Internet, because of the deception or misleading representation of Islam/Muslims found on many websites. However, Islamic resources on the Internet still impact many people in many ways, especially young people. This paper investigates how online audio Qur’an empowers listeners. The online audio Qur’an file can be downloaded and installed on either a mobile device or a PC, or listened to on different websites. The research was carried out through a quantitative survey of 123 respondents; both descriptive and inferential statistic analyses were used to develop and validate a new scale that measures the empowerment through Internet sources of audio Qur’an. The items on the scale measured the key variables that impact people in their use of online audio Qur’an. The result shows that the key attribute empowering listeners is competence.